Implementasi Pendekatan Restorative Justice pada Kasus Penganiayaan di Kepolisian: Analisis Perkara Nomor: BP/07/VII/2024/Reskrim - Anggun Rahma Dewi; Ahmad Irzal Fardiansyah; Fristia Bardian Tamza (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
The application of restorative justice by the police in cases of assault is based on Indonesian National Police Regulation Number 8 of 2021 concerning Handling Criminal Acts Based on Restorative Justice. This regulation provides a basis for investigators in resolving criminal cases by exploring the values ​​of justice that exist in society. This study aims to analyze the application of restorative justice by the police in cases of assault and the inhibiting factors. The research method uses a normative juridical and empirical juridical approach, with secondary data through library research and primary data through field studies. The results indicate that the resolution of cases of assault complies with the provisions of the regulation, as both formal and material requirements are met, and a peace agreement exists between the perpetrator and victim. This process adopts local wisdom values ​​by involving the perpetrator, victim, their respective families, and community leaders. However, obstacles to its implementation exist, including third-party intervention from the victim's family, the perpetrator's limited financial capacity, external interests, lack of community understanding, and communication barriers between the perpetrator and victim. Therefore, specific regulations regarding restorative justice are needed, incorporated into criminal procedural law provisions, for example through the Criminal Procedure Code (RKUHAP), to provide a strong legal basis and ensure legal certainty.